2022
DOI: 10.3389/fpls.2022.1016551
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of coleoptile length with Shanxi wheat

Abstract: In arid and semi-arid regions, coleoptile length is a vital agronomic trait for wheat breeding. The coleoptile length determines the maximum depth that seeds can be sown, and it is critical for establishment of the crop. Therefore, identifying loci associated with coleoptile length in wheat is essential. In the present study, 282 accessions from Shanxi Province representing wheat breeding for the Loess Plateau were grown under three experimental conditions to study coleoptile length. The results of phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Short coleoptiles pose challenges in many cereals often leading to issues such as poor establishment, late emergence, and slow early leaf area development particularly in water-limited growing regions. Previous studies also indicated that strong correlations between CL and drought resistance index (Wang and Zou 1997 ; Hu et al 2007 ) and suggested that CL can be used as a surrogate trait to screen for drought tolerant genotypes at seedling stage (Khadka et al 2020 ; Wei et al 2022 ). Thus, identification of genomic regions contributing to CL is highly valuable to breeding programs.…”
Section: Discussionmentioning
confidence: 98%
“…Short coleoptiles pose challenges in many cereals often leading to issues such as poor establishment, late emergence, and slow early leaf area development particularly in water-limited growing regions. Previous studies also indicated that strong correlations between CL and drought resistance index (Wang and Zou 1997 ; Hu et al 2007 ) and suggested that CL can be used as a surrogate trait to screen for drought tolerant genotypes at seedling stage (Khadka et al 2020 ; Wei et al 2022 ). Thus, identification of genomic regions contributing to CL is highly valuable to breeding programs.…”
Section: Discussionmentioning
confidence: 98%
“…For example, wheat landraces in the Northern Spring Wheat Zone (NS) and the Northwestern Spring Wheat Zone (NWS) in China displayed longer coleoptile lengths compared to landraces from other agro-ecological zones [11]. Another study in wheat also showed that irrigated wheat cultivars have shorter coleoptile lengths compared to dryland cultivars [16]. Additionally, previous studies in wheat [15] revealed that the modern cultivars exhibited significantly shorter coleoptile lengths compared to the landraces.…”
Section: Coleoptile Length Variation In Oatmentioning
confidence: 99%
“…Considerable studies have been carried out to evaluate the coleoptile length in major cereal crops, such as rice [14], wheat [11,15,16], and barley [17,18], revealing a wide range of variation in these crops. In contrast, there is limited information available on the coleoptile length of oat cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…This gene is involved in seed germination, plant growth and development, organ senescence, immunity, and stress response [59]. Among the seedling vigour traits, CL was found to be associated with drought tolerance in wheat due to determining the maximum depth that seeds can be sown, and it is critical for the establishment of the crop [60]. The SNP markers AX-94583923, AX-95017965, and AX-94773224 were associated with CL across the year.…”
Section: Genome-wide Association and Candidate Gene Identificationmentioning
confidence: 99%